Enhancing Early Literacy: The Impact of the Hubbul Ilmii Book on Reading Skills in Malaysian Children Aged 5-6 Years - Hayyu, Harisma Fatihatul; Wulansari, Betty Yulia; Mutaqin, Muhamad Azam; Bustari, Nasriadi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study investigates the impact of the Hubbul ilmii Book on the reading abilities of children aged 5-6 years at SB Al-Ikhlas Kampung Sungai Penchala, Malaysia. Utilising a quantitative, experimental one-group pretest-posttest design, 35 participants underwent an eight-week reading program: Pretest and posttest assessments measured reading proficiency in vocabulary, sentence comprehension, and fluency. Data collection included observations and interviews, analysed using paired sample t-tests. Results demonstrated a significant positive effect, with a p-value of 0.000 and a t-value of 8.276, confirming improved reading skills post-intervention. Specifically, children showed marked improvements in letter recognition, memorisation, distinguishing letters, and reading fluency. The mean difference between pre-test and post-test scores was -4.400, with a standard deviation of 3.145 and a standard error mean of 0.531. These findings align with existing literature, underscoring the book's efficacy in enhancing early literacy. Implications suggest integrating multimedia resources in curricula to bolster language development. However, the study's limitations include its short duration and small sample size, which may affect the generalizability of the results. Further research with larger samples and longer durations is needed to validate these findings and explore long-term impacts. Implications suggest that integrating multimedia resources and age-appropriate books in curricula can significantly enhance language development and reading skills in young children. In conclusion, the Hubbul Ilmii Book effectively improves young children's reading abilities, supporting comprehensive language development and fostering learning confidence. This study advocates for the inclusion of such resources in early childhood education programs to bolster literacy and overall academic achievement.